2022
DOI: 10.1038/s41375-022-01602-4
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the importance and regulation of key enhancers for human MEIS1 expression

Abstract: Myeloid ecotropic virus insertion site 1 (MEIS1) is essential for normal hematopoiesis and is a critical factor in the pathogenesis of a large subset of acute myeloid leukemia (AML). Despite the clinical relevance of MEIS1, its regulation is largely unknown. To understand the transcriptional regulatory mechanisms contributing to human MEIS1 expression, we created a knock-in green florescent protein (GFP) reporter system at the endogenous MEIS1 locus in a human AML cell line. Using this model, we have delineate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…S1A). We used a CALM-AF10 positive AML cell line – U937 - where the enhanced green fluorescence protein (eGFP) is knocked into the endogenous MEIS1 locus immediately upstream of the start codon 14 . Leveraging this system, we sought to comprehensively identify epigenetic regulators of MEIS1 expression as a surrogate for identifying HOX/MEIS regulators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1A). We used a CALM-AF10 positive AML cell line – U937 - where the enhanced green fluorescence protein (eGFP) is knocked into the endogenous MEIS1 locus immediately upstream of the start codon 14 . Leveraging this system, we sought to comprehensively identify epigenetic regulators of MEIS1 expression as a surrogate for identifying HOX/MEIS regulators.…”
Section: Resultsmentioning
confidence: 99%
“…We reasoned that a detailed and systematic identification of epigenetic modulators critical for sustaining HOX/MEIS-activation in AML would help identify novel nodes for targeted drug-discovery campaigns aimed at this clinically important pathway. To this end, we conducted pharmacological and CRISPR-based genetic screens using enhanced green fluorescence protein (eGFP) tagged MEIS1 AML cells 14 . Our screens identified several novel regulators of HOX/MEIS expression in AML and many of them were important for sustaining the expression of an array of leukemia oncogenes that drive AML including BMI1, SATB1 and MYC .…”
Section: Mainmentioning
confidence: 99%
“…MEIS1 plays a crucial role in cellular development and proliferation (Li et al 2022 ). The MEIS1 locus covers around 175 kb of the genome containing several regulatory domains and enhancers (Xiang et al 2022 ). MEIS1 expression has been linked as an oncogene by regulating the proliferation of acute myeloid leukemia (Li et al 2016 ; Xiang et al 2022 ) and prostate cancer (Johng et al 2019 ), migration in pancreatic cancer (von Burstin et al 2017 ), and stemness and epithelial-mesenchymal transition (EMT) capability in esophageal squamous cell carcinoma (Mahmoudian et al 2019 ; Zargari et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The MEIS1 locus covers around 175 kb of the genome containing several regulatory domains and enhancers (Xiang et al 2022 ). MEIS1 expression has been linked as an oncogene by regulating the proliferation of acute myeloid leukemia (Li et al 2016 ; Xiang et al 2022 ) and prostate cancer (Johng et al 2019 ), migration in pancreatic cancer (von Burstin et al 2017 ), and stemness and epithelial-mesenchymal transition (EMT) capability in esophageal squamous cell carcinoma (Mahmoudian et al 2019 ; Zargari et al 2020 ). Conversely, its expression suppresses colorectal (Li et al 2022 ), prostate (Bhanvadia et al 2018 ; VanOpstall et al 2020 ; Whitlock et al 2020 ), lung (Li et al 2014 ), and esophageal (Rad et al 2016 ) cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study was to elucidate the common modulators of miR-23a and NORHA axis in porcine GCs to understand the molecular regulation. We identified MEIS1, an important member of the TALE (transcription activator-like effectors) protein family and a transcription factor of key genes related to various physiological and pathological processes [ 13 , 14 , 15 , 16 ], as a common transcription factor of the miR-23a and NORHA axis in GCs. Furthermore, we also showed that transcription factor MEIS1 forms a small regulatory network with the miR-23a/NORHA axis by inhibiting their transcription, which further inhibits GC apoptosis.…”
Section: Introductionmentioning
confidence: 99%